Comprehensive assessment of laser tube bending process by response surface methodology - Alves de Sousa, Ricardo (2023)
The laser beam can be used as a powerful tool for bending tubes and sheets by local heating and buckling mechanism. In this paper, the bending of mild steel tubes will be investigated by irradiation of the laser beam. To consider the effect of the interaction of process parameters despite previous research, six laser tube bending process parameters in different levels including laser power, scanning speed, laser beam diameter, irradiation length, number of irradiation passes, and irradiation scheme are selected and set of 92 experimental tests planned according to the response surface methodology (RSM). The tests have been carried out by using a continuous wave (CW) CO2 laser. The influencing parameters affecting the main bending angle and lateral bending angle are determined. The effect of main process parameters and their interaction on the main and lateral bending angle are discussed either. The AIS creates a higher main bending angle compared to the CIS. The results show that the main bending angle and lateral bending angle increase by increasing the laser power, irradiation length, and the number of irradiation passes and reducing the scanning speed and laser beam diameter. The main and lateral bending angles are determined by a regression equation with about 96% goodness of fitting. The results show that 1100 W laser power, 14.6 mm/s scanning speed, 4 mm laser beam diameter, 28.27 mm irradiation length, 1 pass of irradiation, and axial irradiation scheme (AIS) lead to a simultaneous maximum bending angle of 1.80° and minimum lateral bending angle of 0.152°.